THE EFFECT OF SERVICE QUALITY, PRICE, AND BRAND IMAGE ON CUSTOMER SATISFACTION USING ONLINE OJEK TRANSPORTATION SERVICES - Putri, Ghinadya Canceriani; Hafidzi, Achmad Hasan; Nursaidah, Nursaidah (Dynamic Management Journal, 2024)
This research aims to determine the influence of service quality, price and brand image on Gojek consumer satisfaction in the Tapal Kuda area. A sample of 150 respondents from the Gojek consumer population in the Tapal Kuda area was used for this research through a questionnaire. The sampling method used in this research was a non-probability sampling technique using purposive sampling with sample characteristics such as respondents who had used Gojek services, especially Go-Ride, at least twice, aged over 17 years and in the Tapal Kuda area. The test equipment used to test this research instrument consists of validity tests, reliability tests and classical assumption tests. The data analysis technique uses multiple linear analysis. To facilitate research, hypothesis testing was carried out using the t-test and SPSS version 29 software. The research results showed that the service quality variable had a significant influence on customer satisfaction. The price variable had a significant influence on customer satisfaction. The brand image variable had a significant influence on satisfaction customer